2020
DOI: 10.1093/ofid/ofaa436
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Distribution and Predictors of Mortality in Hospitalized Patients With COVID-19: A Cohort Study

Abstract: Background The global Coronavirus Disease 2019 (COVID-19) pandemic offers the opportunity to assess how hospitals managed the care of hospitalized patients with varying demographics and clinical presentation. The goal of this study is to demonstrate the impact of densely populated residential areas on hospitalization and to identify predictors of length of stay and mortality in hospitalized patients with COVID-19 in one of the hardest hit counties internationally. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Although classification of patients by EOSS staging resulted in a significant difference in age and sex between the EOSS stages, both of which are known risk factors for poor COVID‐19 outcomes, 6 , 27 , 38 multivariable analyses were adjusted for age and sex, which indicates that the significant associations found are independent of age and sex effects. Moreover, patients may have been misclassified as we tailored our classification scheme to the available data.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although classification of patients by EOSS staging resulted in a significant difference in age and sex between the EOSS stages, both of which are known risk factors for poor COVID‐19 outcomes, 6 , 27 , 38 multivariable analyses were adjusted for age and sex, which indicates that the significant associations found are independent of age and sex effects. Moreover, patients may have been misclassified as we tailored our classification scheme to the available data.…”
Section: Discussionmentioning
confidence: 96%
“…Increased rates of AKI in this population may mediate the association between EOSS stage and poor clinical outcomes as AKI itself has been shown to be a strong predictor of in‐hospital mortality and other poor outcomes in COVID‐19. 27 , 28 Notably, no hospitalized patients with elevated BMI and no or minimal obesity‐related comorbidities (i.e. EOSS stage 0) died, required mechanical ventilation or developed AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included studies, more than half investigated the association of COVID-19 mortality with sociodemographic characteristics such as age and sex, 10,12,[18][19][20][21][22][23][24][25][26][27][28] pointing out that age from 65 years and being male are risk factors for deaths. 10,18,20,22,26 It was also noted that comorbidities were associated with the outcome of death and constituted important risk factors, 1,11,18,20,23,[27][28][29][30][31][32] especially those resulting from cardiovascular complications, especially hypertension and diabetes mellitus (DM).…”
Section: Resultsmentioning
confidence: 99%
“…Another study from Stony Brook University reported that both proteinuria and hematuria at the time of admission were associated with poor outcomes in hospitalized patients with COVID-19 ( 7 ). In addition, in patients requiring mechanical ventilation, acute kidney injury was the highest predictor of mortality ( 8 ).…”
Section: Introductionmentioning
confidence: 99%